The validity of central venous to arterial carbon dioxide difference to predict adequate fluid management during living donor liver transplantation. A prospective observational study - Mohamed ELAyashy; Hisham Hosny; Amr Hussein; Ahmed AbdelAal Ahmed Mahmoud; Ahmed Mukhtar; Amira El-Khateeb; Mohamed Wagih; Fawzia AboulFetouh; Amr Abdelaal; Hany Said; Mostafa Abdo (BMC Anesthesiology, 2019)
Abstract Background To assess the validity of central and pulmonary veno-arterial CO2 gradients to predict fluid responsiveness and to guide fluid management during liver transplantation. Methods In adult recipients (ASA III to IV) scheduled for liver transplantation, intraoperative fluid management was guided by pulse pressure variations (PPV). PPV of ≥15% (Fluid Responding Status-FRS) indicated fluid resuscitation with 250 ml albumin 5% boluses repeated as required to restore PPV to < 15% (Fluid non-Responding Status-FnRS). Simultaneous blood samples from central venous and pulmonary artery catheters (PAC) were sent to calculate central venous to arterial CO2 gap [C(v-a) CO2 gap] and pulmonary venous to arterial CO2 gap [Pulm(p-a) CO2 gap]. CO and lactate were also measured. Results Sixty seven data points were recorded (20 FRS and 47 FnRS). The discriminative ability of central and pulmonary CO2 gaps between the two states (FRS and FnRS) was poor with AUC of ROC of 0.698 and 0.570 respectively. Central CO2 gap was significantly higher in FRS than FnRS (P = 0.016), with no difference in the pulmonary CO2 gap between both states. The central and Pulmonary CO2 gaps are weakly correlated to PPV [r = 0.291, (P = 0.017) and r = 0.367, (P = 0.002) respectively]. There was no correlation between both CO2 gaps and both CO and lactate. Conclusion Central and the Pulmonary CO2 gaps cannot be used as valid tools to predict fluid responsiveness or to guide fluid management during liver transplantation. CO2 gaps also do not correlate well with the changes in PPV or CO. Trial registration Clinicaltrials.gov Identifier: NCT03123172. Registered on 31-march-2017.